PENGARUH SUBSTITUSI SARI DAUN SIRSAK TERHADAP KUALITAS ES KRIM - Putri, Suki Ayu; Faridah, Anni; Syarif, Wirnelis (Journal of Home Economics and Tourism, 2017)
This research was based on the number of people who do not know and do not like soursop leaf juice. Though the nutrients contained in it is very good for the body. This study aims to analyze the effect of soursop leaf substitution of 0%, 25%, 50%, 75% on ice cream quality (color, aroma, texture, and taste). The types of studies conducted by the method of pure experimentation RAL. Variables used are variable X (soursop leaf substitution) and Variable Y (ice cream quality). The data used was obtained directly from a 30 person semi trained panelists. The data analysis technique is ANAVA, if different real continued with test Duncan. The results showed that was an influence of soursop leaf substitution on green color quality, aroma of milk, sweet taste and hedonic aroma of milk, soft texture and sweet taste of ice cream. The quality of soft texture and color hedonic there is no real effect. Best quality ice cream using soursop leaves as much as 25% (X1).Keywords: Ice Cream, Soursop, and Quality